Faktor Ekonomi dan Pertumbuhan Ekonomi Terhadap Kemiskinan di Kalimantan - Saputro, Firdaus Budhy; Fitria, Dona; Widiyarini, Widiyarini (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This study describes the relationship between economic factors, economic growth, and poverty in Kalimantan, an island rich in natural resources in Indonesia. Economic factors, including natural resource exploitation, infrastructure investment, and government policies, were found to play a crucial role in driving economic growth. Despite significant economic growth, unequal income distribution is a major challenge, with a number of communities still experiencing poverty. Environmental and social impacts are also the focus of the study, considering that rapid economic growth is often accompanied by environmental damage and social inequality. The government's role in managing the impacts of economic growth is very important, with the need for policies that support economic diversification, fair income distribution, and environmental protection. This study highlights the need for a holistic regional development strategy, which takes into account the balance between economic growth, distribution of benefits and environmental sustainability. Policy recommendations include economic diversification, infrastructure strengthening, social protection policies, and sustainable environmental management. The conclusion emphasizes the importance of overcoming unequal income distribution, maintaining a balance between economic growth and the environment, and increasing the inclusiveness of economic development to reduce poverty levels in Kalimantan.